PEMBUATAN MINUMAN HERBAL JAHE SERBUK DAN NATA LIDAH BUAYA DARI TANAMAN OBAT KELUARGA (TOGA) DI NAGARI SIKUCUR KECAMATAN V KOTO KAMPUNG DALAM KABUPATEN PADANG PARIAMAN - Dira Hefni; Netty Suharti; Yoneta Srangenge (LPPM Universitas Andalas, 2022)
TOGA (Family Medicinal Plant) is a type of plant that is cultivated around the yard or yard of thehouse and has a function as a medicinal plant. TOGA can be used to reduce the use of modern medicineswhich tend to be expensive and have many side effects. The existence of TOGA in the home environmentis very important. The use of TOGA in self-medication provides a cheap, fast, and convenient solution inovercoming minor ailments. Counseling and education to the public regarding the use of TOGA plantsare expected to encourage people to